CRISPR-based assay for the molecular identification of highly prevalent Salmonella serotypes. (May 2018) - Bugarel, Marie; Bakker, Henk den; Grout, Joel; Vignaud, Marie-Leone; Loneragan, Guy H.; Fach, Patrick; Brisabois, Anne
Highlights: Innovative serotyping method for highly prevalent Salmonella serotypes. Use of CRISPR spacers suitable for serotype determination. CRISPR spacer content diversity associated with geographical origin of the strains. Validation study combining experimental and in silico investigations.